Evaluation of Lagergren Kinetics Equation by Using Novel Kinetics Expression of Sorption of Zn2+ onto Horse Dung Humic Acid (HD-HA) - Bambang Rusdiarso; Rahmat Basuki; Sri Juari Santosa (Indonesian Journal of Chemistry, 2016)
Extraction and purification of humic acid from dry horse dung powder (HD-HA) was performed successfully and the purified HD-HA was then applied as sorbent to adsorb Zn2+. Extraction and purification were performed based on procedure of Stevenson (1994) under atmospheric air. Parameters investigated in this work consist of effect of medium sorption acidity, sorption rate (ka) and desorption rate constant (kd), Langmuir (monolayer) and Freundlich (multilayer) sorption capacities, and energy (E) of sorption. The ka and kd were determined according to the kinetic model of second order sorption reaching equilibrium, monolayer sorption capacity (b) and energy (E) were determined according to Langmuir isotherm model, and multilayer sorption capacity (B) was determined based on Freundlich isotherm model. Sorption of Zn2+ on purified HD-HA was maximum at pH 5.0. The novel kinetic expression resulted from proposed kinetic model has been shown to be more applicable than the commonly known Lagergren equation obtained from the pseudo-first order sorption model. The application of the equation revealed that the intercept of Lagergren equation, ln qe was more complex function of initial concentration of Zn2+ (a), Langmuir sorption capacity (b), and sorbed Zn2+ at equilibrium (xe).